Myoglobin and left ventricular ejection fraction as predictive markers for death in children with fulminant myocarditis - Xie, Tingting; Zang, Xiaodong; Xiong, Yingying; Yang, Chaolei; Li, Fei; Wang, Dandan; Shu, Yaqin; Mo, Xuming; Chen, Mingwu (Frontiers in Pediatrics, 2022)
Background: Fulminant myocarditis (FM) is an inflammatory process of the myocardium that is an important cause of cardiac dysfunction in children and is characterized by rapid onset, acute progression, and high mortality. The study sought to describe the clinical characteristics and prognostic factors in children with FM. Methods: The study population consists of 37 consecutive patients admitted from May 2014 to December 2021 with a diagnosis of FM. All the children were admitted to the First Affiliated Hospital of USTC, Division of Life Science and Medicine, University of Science and Technology of China (Anhui Provincial Hospital) and Children’s Hospital of Nanjing Medical University intending to summary predictors of death in FM. Results: A total of 37 children with FM had an average age of 8.35±4.36 years old. 25 patients survived and 12 patients died. 25 children were discharged from the hospital after a series of active rescue treatments such as nutritional myocardial drugs,high-dose intravenous immunoglobulin (IVIG),glucocorticoids(GC)and temporary pacemaker(TP), extracorporeal membrane oxygenation(ECMO), and continuous renal replacement therapy(CRRT). 12 children were classified as death group due to resuscitation failed. The levels of procalcitonin(PCT), creatine kinase(CK), and myoglobin(MYO)in the death group were all higher than those in the survival group(all P<0.05), and the left ventricular ejection fraction (LVEF)in the death group was significantly lower than that in the survival group(P=0.002). Binary logistic regression analysis revealed that MYO [OR:1.006; 95%CI:(1.000-1.012);P=0.045] and LVEF[OR:0.876;95% CI: (0.785-0.978);P=0.019]were independent predictors of FM. ROC curve analysis showed that the area under ROC curve(AUC)of MYO,LVEF and combined prediction probability was [AUC:0.957;95%CI:0.897~1.000], [AUC:0.836;95%CI:0.668~1.000] and[AUC:0.972;95%CI:0.916~1.000], respectively,indicating that the accuracy of combined predictive markers for death was higher than that of any single marker with the sensitivity of 100% and the specificity of 96.0%. Conclusion: The levels of MYO and LVEF can be as markers for prognosis of FM, which can effectively evaluate the disease severity. Their combination can improve forecast accuracy,thus the detection of above-mentioned indexes are possessed of higher value for clinical applications.